Gerakan Kepanduan Pramuka dan Pesantren: Pendekatan Moderasi dan Deradikalisasi - Rozi, Fathor (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This research discusses the role of the Scout Movement and Islamic Boarding Schools as agents for character formation and overcoming radicalism among Islamic students. By using a moderation and deradicalization approach, this research explores how these two institutions can collaborate in forming moderate attitudes and preventing potential radicalism among the younger generation. This research method involves interviews, observation and documentation to gain in-depth insight into the moderation programs implemented in the Scout Movement and Islamic boarding schools. Research findings show that the moderation approach in these two institutions includes character education, interfaith dialogue, and balanced development of leadership skills. Apart from that, deradicalization efforts are carried out through a deep understanding of national values, tolerance and intercultural dialogue. The results of this research provide conceptual and practical insights regarding how the Scout Movement and Islamic boarding schools can become effective instruments in responding to the challenges of radicalism. The implications of these findings involve the development of more structured and collaborative moderation programs between educational and religious institutions, aimed at forming the character of the younger generation who are responsible, moderate, and able to maintain diversity in society.